Morphology, microstructure and mechanical properties of synthesized nano-sized alumina - Dela Cuesta, Lina C.
Alumina powders were synthesized from aqueous solutions of ammonium aluminum sulfate (AA) and ammonium hydrogen carbonate (AHC) at pH 6.5 and pH 8.5. In acidic medium (pH 6.5), the alumina immediately precipitated, whereas in basic medium (pH 8.5), the alumina precipitate remained dispersed and took time to settle. Based on the XRD analysis, the powder prepared at pH 6.5 was Al (OH)3 and had an amorphous structure. On the other hand, the powder made at pH 8.5 was ammonium aluminum carbonate hydroxide (AACH) and gave a crystalline structure. Both powders exhibited fine particle size, although the amorphous one was coarser.